2022
DOI: 10.1134/s1021443722020212
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and the Energy Status of Plant Cells

Abstract: In plant cells the homeostatic control of energy balance involves the production and recycling of adenylates with macroergic bonds, ATP and ADP. The maintenance of anabolic processes requires the relative saturation of the adenylate pool with high energy phosphoanhydride bonds. The bulk of ATP synthesis is carried out both in mitochondria and in chloroplasts while optimal ATP levels within other cell compartments are maintained by adenylate kinases (AK). AK activity was recently found in cytosol, mitochondria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…So, the enhanced expression of amino acid metabolism genes (Figure 5a,b) under such favorable trophic conditions is not surprising. Nevertheless, under nutrient depletion or starvation conditions, the increased demand for respiratory substrates occurs [44] and the acquisition of such substrates is remarkably easier from the degradation of storage protein than from storage lipid. If the source of respiratory and anabolic substrates is storage protein, amino acids are released from albumins and globulins (in lupins they are mainly globulins, constituting up to 80% of all storage proteins [1]) by the action of endo-and exopeptidases [20], and such amino acids are almost ready to supply the respiration.…”
Section: Discussionmentioning
confidence: 99%
“…So, the enhanced expression of amino acid metabolism genes (Figure 5a,b) under such favorable trophic conditions is not surprising. Nevertheless, under nutrient depletion or starvation conditions, the increased demand for respiratory substrates occurs [44] and the acquisition of such substrates is remarkably easier from the degradation of storage protein than from storage lipid. If the source of respiratory and anabolic substrates is storage protein, amino acids are released from albumins and globulins (in lupins they are mainly globulins, constituting up to 80% of all storage proteins [1]) by the action of endo-and exopeptidases [20], and such amino acids are almost ready to supply the respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Adenylate Energy Charge (AEC) was calculated as (ATP + ½ ADP) / (ATP + ADP + AMP) according to Tyutereva et al, 2022, based on the relative concentration of ATP, ADP and AMP obtained by IC-MS after normalization to the internal standard thio-ATP.…”
Section: Methodsmentioning
confidence: 99%
“…The carrier theory states that carriers encounter specific ions for which they have attraction, from carrier ion centres, and pass across membranes, then, the enzyme phosphatase situated at innermost membrane-bound increases, splits off phosphate from carrier complexes, and ions are discharged (Mengel and Kirkby, 1978;Alaoui et al, 2022). Marschner (1995) and (Tyutereva et al, 2022) observed that, in this transport process, energy is essential and participation of adenosine triphosphate (ATP) is usually rec ounted. Fageria et al (2006) and Griffiths and York (2020) reported that high energy molecule ATP is produced from adenosine diphosphate (ADP) = inorganic P (Pi) from respiration (oxidative phosphorylation reactions).…”
Section: Carrier Ion Transport Theorymentioning
confidence: 99%